Empirical Implementation of Industry 4.0 Model among Malaysian and Nigerian SMEs - Maruf Gbadebo Salimon; Haim Hilman Abdullah; Abdullahi Hassan Gorondutse; Shahmir Sivaraj Bin Abdullah; Abdullahi Tafida; Yusha’u I. Ango; Hellen Andow; Ahmed B. Abdul-Qadir (International Journal of Supply Chain Management, 2019)
The primary objective of this study is to examine the factors that influence the implementation of Industry 4.0 among Malaysian and Nigerian Small and Medium Enterprises. The Questionnaires were distributed to SMEs operators in both countries while analysis was done with 74 and 95 responses from Malaysia and Nigeria respectively using Partial Least Square Structural Equation Modelling (PLS-SEM 3). Based on the findings from Malaysian data, information access, cost reduction, and efforts coordination significantly and positively influence the implementation of IR 4.0 while reluctance behaviour is not significant. For Nigerian data, information access, reluctance behaviour and effort coordination significantly and positively influence implementation of Industry 4.0 while effort coordination is not significant. The implications for both academia, practitioners, and policy makers are highlighted.